Ecosanctuaries, grassroots community development and partnerships with tāngata whenua : a postdevelopment perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of International Development at Massey University, Palmerston North, Aotearoa New Zealand - Burnett, Scott (Massey University, 2022)
Aotearoa New Zealand is in the midst of a human-induced biodiversity crisis, with three-quarters of birds, reptiles and frogs at risk of extinction. Last year a redeveloped National Biodiversity Strategy called Te Mana o te Taiao was released. The strategy argues that we need to change people's relationship with the natural world in order to address biodiversity loss. In this thesis, I explore the socio-cultural aspects of three community-led ecosanctuary projects to examine this problem and illuminate a pathway toward a more sustainable relationship between people and the natural world. I use a hopeful postdevelopment lens, which seeks to imagine and practise development differently through research couched in hope and possibility. It builds upon postdevelopment's insight that over-reliance upon universally applied, science-based, market-driven technological solutions often delivers unintended negative outcomes and devalues alternative perspectives. A qualitative approach was employed for this research, using semi-structured interviews with key informants, an analysis of documents published by these organisations, and a synthesis of the published literature. The research illustrates how dominant Western paradigms, which see humans as separate from the natural world, have contributed to the biodiversity crisis. It then reveals that awareness of the state of the environment does not necessarily result in behaviour change, and I argue that the adoption of indigenous approaches may help turn knowledge into action for the environment. I found ecosanctuaries are well-placed to enact this paradigm change in human-nature relationships and are already doing so as a side-effect of their activities rather than with a planned focus. The research further examined the influence of ecosanctuaries upon their communities, how ecosanctuaries worked with indigenous peoples, and how they incorporated indigenous knowledge. These findings can be used by community conservation initiatives to articulate the benefits such projects deliver to their communities and suggest how stronger relationships with tāngata whenua can be developed and why this is valuable.
Keywords: 410406 Natural resource management; 450903 Te whāomoomo taiao o te Māori (Māori environmental conservation)